The implications of nutrition services within the health care system on the quality of life and longevity, in developed countries: a re-analysis of 38 studies - Tyrovolas, Stefanos; Tountas, Yannis; Polychronopoulos, Evangelos; Panagiotakos, Demosthenes B (Central European Journal of Public Health, 2011)
Background: The United Nations' Global Population Pyramid is undertaking a shift from pyramid to cube. The concomitant decline in fertility and mortality rates produces a higher portion of older people, and, thus, an increased number of deaths due to cancer and cardiovascular disease (CVD). Limited studies have investigated the effect of health care services on longevity. In this work, findings from studies throughout the world are presented and re-analysed in order to evaluate the effect of health care services on population's health status. Methods: Studies that have assessed the associations of nutritional and other health care services (i.e., physicians supply, technical support, inter-collaboration) on longevity and health status were retrieved (searches in PubMed, EMBASE, Scopus, up to January 2010), and summarized here. Results: Few studies, mostly located in the US and the UK, have evaluated the role of health care services on population's health status. The majority of the studies reported a beneficial association between the frequency of physicians and mortality, while some other studies reported weak or no associations between physician's supply and longevity. Also nutritional services (screening) seem to promote better clinical outcome. Conclusion: Although very few data are available, it seems that there is a positive correlation between the quality and quantity of health care services and longevity. Strong primary health care seems to be effective on the population's health outcome. Active health policy and enhance-ment of health and nutritional services within the health care system may contribute to improved population's health and their overall quality of life.
Keywords: nutriční terapie; zdravotní stav; Primary Health Care; primární zdravotní péče; kvalita života; Health Services; Longevity; Health Status; lidé; Quality of Life; vyspělé země; Developed Countries; Humans; dlouhověkost; Nutrition Therapy; zdravotnické služby